A Rare Case Report on Thoracoomphalopagus - Lamichhane, Sabina; Banerjee, B; Subedi, S (Nepal Journal of Obstetrics and Gynaecology, 2016)
In the present case study we are reporting a case of thoracoomphalopagus conjoined twins. A 24 years old gravida two para 0+1 carrying thoracoomphalopagus conjoined twins was diagnosed by ultrasonography at early second trimester with single placenta attached posteriorly and low lying. The mortality and morbidity of conjoined twins are high so making the early diagnosis with ultrasonographic examination provides the parents a chance to elect for pregnancy termination.